Social entrepreneurship: An overview - Shaffie, Fuziah; Yusof, Ab. Aziz; Wan Abdullah, Wan Abd Rahman Khudzri; Wan Ahmad, Wan Ibrahim; Bahari, Azizan (2012)
Social entrepreneurship scholars are in the midst of a number of debates involving definitional and conceptual clarity, boundaries of the field, and a struggle to arrive at a set of relevant and meaningful research.The existence of social entrepreneurship-oriented social work practitioner can bring about new impetus to the approach in trying to find solutions to social problems faced by the community.The data for this study is derived from a research about social entrepreneurship conducted on social work practitioners in the Northern parts of Peninsular Malaysia.Though it is not written to either present the findings of the study, it could well-trigger ideas for researchers, however.The paper draws on the work of others and to this adds personal conclusions from the literatures and observations.It attempts to deal with complex issues and tensions in a straightforward style and thus draw attention to key debates.This conceptual discussion paper aims to contribute to the literature on social entrepreneurship.It draws on published work to flag key issues and discussion points that affect the clarity of the understanding.It aims to provide some greater insight and help both scholars and practitioners in their respective quests for understanding and improvement.This paper also discusses the meaning of social enterpreneurship and the differences between traditional or conventional entrepreneurship and the characteristics of social entrepreneurship.Social entrepreneurship has social responsibility, and its main concern is not economic profit.It is seen more as an agent of change than a profit-seeking enterprise.The goals of entrepreneurial are to ensure that issues of social and community problems can be resolved as well as to conduct activities to generate profits.The paper discusses the expected challenges faced by the entrepreneurs.Finally, the paper also provides some examples of successful social entrepreneur locally and internationally.